1980
DOI: 10.1143/jjap.19.l375
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Oxygen into Silicon during Pulsed-Laser Irradiation

Abstract: Evidence for the oxygen incorporation into silicon during surface melting by the pulsed-laser irradiation is presented. SIMS measurement of 18O in Si samples which were laser-irradiated in 18O2 atmosphere shows that 18O is introduced in Si with the maximum concentration 7×1020 cm-3 and the penetration depth 1.4 µm. The incorporation of 18O is blocked when the Si surface is covered with SiO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 2 publications
4
10
0
Order By: Relevance
“…These contaminants are more likely to penetrate into the material during the melting period and are influenced by the process environment and the doping source. High levels of oxygen in the melt area were measured by some research groups 22–24. Koichiro Hoh 23 measured oxygen levels of 10 18 –10 21 cm −3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These contaminants are more likely to penetrate into the material during the melting period and are influenced by the process environment and the doping source. High levels of oxygen in the melt area were measured by some research groups 22–24. Koichiro Hoh 23 measured oxygen levels of 10 18 –10 21 cm −3 .…”
Section: Introductionmentioning
confidence: 99%
“…High levels of oxygen in the melt area were measured by some research groups 22–24. Koichiro Hoh 23 measured oxygen levels of 10 18 –10 21 cm −3 . Such high concentrations can create micro‐defects and influence the electrical performance of the device 25.…”
Section: Introductionmentioning
confidence: 99%
“…The "Type II" regime is accompanied by the silicon oxidation, apparent due to the enhanced oxygen incorporation into the silicon lattice at high pulse energies. 28,39 As a result, form birefringence is reduced to À0.4 due to the refractive index change from crystalline silicon to silica glass ( Fig. 4(a)).…”
mentioning
confidence: 99%
“…Consequently, in terms of a thermal melting model, "a native oxide layer cannot be dissolved in Si during pulsed laser melting. As "a matter of fact, Hoh et al [18] have found already that the introduction of 180 in Si which was laser irradiated in 1802 atmosphere, giving rise to concentrations well above the solid solubility of oxygen in Si, was blocked when the Si surface is covered with Si0 2 . On the other hand, our results are in strong contradiction with those of Garulli et al [19], who state that a 1.5 J/cm 2 , 20 ns pulse air anneal of Si causes an oxygen super saturation in the molten region, which oxygen concentration is distributed such that a peak is present in the middle region of this area.…”
Section: Resultsmentioning
confidence: 99%